2006
DOI: 10.2320/matertrans.47.1523
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Melt-Spun Amorphous Ni-Nb-Zr Alloys after Hydrogen Charging

Abstract: The effect of pre-charged hydrogen on the mechanical behavior of melt-spun amorphous Ni-Nb-Zr alloys was investigated. A substantial increase in the tensile fracture strength is observed even in hydrogen content up to about 46 at%. The Vickers hardness gradually increases with an increase in hydrogen content up to about 27 at%, and keeps almost the same value in the higher content more than 46 at%. It might be said that the amorphous (Ni 0:6 Nb 0:4 ) 70 Zr 30 alloy is not embrittled distinctly even in the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
(19 reference statements)
3
11
0
Order By: Relevance
“…Thickness and width of the fabricated samples is about 10-15 μm and 1 mm, respectively. Hydrogenation was carried out electrolytically as described elsewhere [10]. The amount of the hydrogen absorbed in the sample was analyzed by the inert gas carrier meltingthermal conductivity method.…”
Section: Methodsmentioning
confidence: 99%
“…Thickness and width of the fabricated samples is about 10-15 μm and 1 mm, respectively. Hydrogenation was carried out electrolytically as described elsewhere [10]. The amount of the hydrogen absorbed in the sample was analyzed by the inert gas carrier meltingthermal conductivity method.…”
Section: Methodsmentioning
confidence: 99%
“…In the previous report by Kawashima et al, it has been pointed out that the morphology of the NiNbZr amorphous alloy ribbons changed after electrochemically charging with time. 4) They showed that the ribbon specimens always curled and gradually returned to the originally straight shape. Although the behavior has been thought to be due to the homogenization of hydrogen distribution in the specimen, timedependencies of some physical properties have not been investigated.…”
Section: ¹2mentioning
confidence: 99%
“…2,3) The value of the permeability exceeds that of the Pd, thus, the NiNbZr amorphous alloys have been thought to exhibit high potential as applicable materials. Mechanical properties of the hydrogen absorbed amorphous ribbons were also investigated by Kawashima et al 4) Very recently, interesting electrical transport properties, such as ballisticconductivity, superconductivity and the Coulomb-blockade oscillations have been found in the hydrogen absorbed [(Ni 0.6 Nb 0.4 ) 1¹x/100 Zr x/100 ] 100¹y H y (30 < x < 50, 0 < y < 20) amorphous alloy ribbons by Fukuhara et al 5,6) Especially for x = 40, it has been shown by their reports that the ballisticconductivity, where, the electrical resistivity suddenly decreased to triple order, was observed when y = 3.9. The superconducting behavior whose onset is 9 K and the Coulomb-blockade oscillations were observed when y = 5.7 and 9.3, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yamaura et al reported that melt-spun Ni ZrNb amorphous alloy, Ni 30 Zr 50 Nb 30 has the excellent hydrogen permeability [5]. The inuence on mechanical properties of the alloys by hydrogen-charge also was investigated, as well [6]. Fukuhara et al observed some new interesting phenomena in the NiZrNbH amorphous alloys besides the high hydrogen permeability.…”
Section: Introductionmentioning
confidence: 97%